Effects of Pristane Alone or Combined with Chloroquine on Macrophage Activation, Oxidative Stress, and Th1/Th2 Skewness - Qiufang Ouyang; Ziyang Huang; Zhenhua Wang; Xiaoqing Chen; Jingqin Ni; Ling Lin (Journal of Immunology Research)
We investigated the protective role of chloroquine against pristane-induced macrophage activation, oxidative stress, and Th1/Th2 skewness in C57BL/6J mice. Those mice were treated with pristane alone or combined with chloroquine. Hematological and biochemical parameters, macrophage phagocytic function, the oxidant/antioxidant index, cytokine for IFN-γ, TNF-α, IL-4, and IL-6, and the isotypes of IgG2a and IgG1 were determined. And the expression of T-bet/GATA-3 and IL-12/IL-10 mRNA in spleen were analyzed by real-time PCR. We found that pristane treatment for a period of 12 or 24 weeks triggered macrophage activation syndrome, characterized by hemophagocytosis in spleen and peripheral blood, enhanced lipid phagocytosis by peritoneal macrophages in vitro, erythropenia and leucopenia, increased anti-Smith, lactic dehydrogenase, triglyceride, and ferritin, as well as hypercytokinemia of IFN-γ, TNF-α, IL-4, and IL-6. In parallel, a significant increase in lipid peroxidation and a decrease in superoxide dismutase, glutathione, and catalase activity, as well as a skewed Th1/Th2 balance in spleen, were observed. However, chloroquine supplementation showed a remarkable amelioration of these abnormalities. Our data indicate that pristane administration induces macrophage activation, oxidative stress, and Th1/Th2 skewness, which can be attenuated by chloroquine.